SUN-036 Evaluation of Gender Experience Among Individuals with Isolated GnRH Deficiency Compared to Controls - Persky, Rebecca (J Endocr Soc, 2020)
Background: Sex hormones play a role in gender identity development. For example, 46,XY individuals with complete androgen insensitivity typically have a female gender identity. Isolated GnRH deficiency (IGD) leads to hypogonadism due to decreased GnRH-induced gonadotropin production. It is unknown if decreased sex hormone exposure leads to differences in gender identity among individuals with IGD compared with the general population. Our objective was to determine if the gender identity in subjects with IGD differs from controls. Methods: We distributed a validated questionnaire; the Gender Identity/Gender Dysphoria Questionnaire for Adults and Adolescents (GIDYQ-AA) (1), to IGD participants who previously enrolled in a phenotyping study. Subjects also provided their age, sex assigned at birth (SAAB), gender and information about their condition and treatment. Group survey scores are expressed as mean ± SD. IGD subject scores were compared with control data (Student’s t-test) obtained from a validation study for the GIDYQ-AA (2). Results: Out of 79 subjects who were contacted, 8 males (M) assigned at birth and 7 females (F) assigned at birth chose to participate and one person actively declined. Average age was 30 y for F and 28 y for M. At the time of the study, all subjects were on hormone supplementation except for one F. A score of 5 indicates a gender identity congruent with SAAB. Among F, mean scaled IGD score was 4.73 ± 0.29 vs. controls (4.8 ± 0.28, n=57; not significant (ns)), and for M it was 4.62 ± 0.52 vs. controls (4.82 ± 0.24, n=37; ns). One female identified as “non-gendered”, one male identified as “intersex/DSD” (14% of respondents), one female did not respond and gender was congruent with SAAB in the remainder. The lowest mean score for an individual question for the IGD F group was in response to whether they felt satisfied being a woman and for the IGD M group, it was in response to whether they felt they were a real man. Conclusions: Men and women with IGD did not show a significant difference in their gender identity compared with controls, and gender was found to be congruent with SAAB for the majority. However, the individual question responses and the self-described gender in this small cohort may suggest that there are differences in how some individuals with IGD experience their gender development. We speculate that this may be related to how they perceive the differences in physical development that they experienced related to their condition. Larger studies in participants with IGD and other disorders that alter sex hormone production/effect are necessary to further understand the relationship between decreased sex hormone exposure during critical developmental periods and gender identity development. References: (1) Deogracias, J.J, et al. J. Sex Res., 2007, 44:4, 370–379 (2) Singh, D. et al. J. Sex Res. 2010, 47:1, 49–58